Synthesis and Anticonvulsant Activity of Prodrug of Gabapentin - Namdeo, K.P.; K. Shrivastava, Sushant (Asian Journal of Chemistry, 2010)
The synthesis and evaluation of anticonvulsant activity of prodrugs of gabapentin are reported by taking the dihydropyridine compound as carrier molecules, in redox delivery approach. A redox system of drug delivery based on an interconvertible dihydropyridine <—–>pyridinium salt carrier. Anticonvulsant activity of all the compounds were tested by chemo-convulsion method and all the compounds found active. All the compounds were also studied for oxidation in various biological fluids and found to be stable and shows sustained release profile which follow first order kinetics. Oxidized form of the conjugate inside the brain act as prodrug, which on hydrolysis yields parent drug.